Isomorphisms of some algebras of analytic functions of bounded type on Banach spaces - S.I. Halushchak (Математичні Студії)
The theory of analytic functions is an important section of nonlinear functional analysis. In many modern investigations topological algebras of analytic functions and spectra of such algebras are studied. In this work we investigate the properties of the topological algebras of entire functions, generated by countable sets of homogeneous polynomials on complex Banach spaces.